Penerapan metode geolistrik tahanan jenis konfigurasi wenner untuk menentukan penyebaran lindi di Tempat Pemprosesan Akhir (TPA) sampah Air Dingin Kota Padang (The application of the wenner configuration resistivity geoelectric method to determine the distribution of leachate in the final waste processing in Air Dingin Padang City) - Yori Deswita; Nofi Yendri Sudiar; Fatni Mufit; - Akmam (PILLAR OF PHYSICS, 2015)
TPA Air Dingin are landfills located in Padang and positioned near the inhabitant area. The accumulationof waste at TPA Air Dingin can cause environment pollution. The  aimed  of  this  research  is  to  determine  the resistivity and the spread  of  leachate in TPA Air Dingin. Estimation of the distribution of leachate below the ground surface use a Resistivity Geoelectrical method with Wenner Configuration. Data were collected by ARES Multielectrode in 3 lines. The data were interpreted using Robust inversion to obtain a 2D model of earth’s surface that consists of depth and resistivity value. The result of this research showed that the kinds of rocks in this area consist of Groundwater, Clay, Sandstone and Andesite. Direction of spread of leachate on the measurements, the distribution of leachate moving from the southeast towards the Northwest